THE CORRELATION BETWEEN STUDENTS’ MASTERY OF GRAMMAR AND THEIR WRITING SKILL IN NARRATIVE TEXT OF THE TENTH GRADE STUDENTS AT VOCATIONAL SCHOOL - Risti Nurlaili; Zuhad Ahmad (Universitas PGRI Palembang, 2026)
This study aimed to investigate the correlation between students’ grammar mastery and their narrative writing skill among tenth-grade students at SMK Adi Luhur. A quantitative correlational research design was employed to examine the relationship between the two variables. The participants of this study were 75 students selected through random sampling from a population of 112 tenth-grade students. Data were collected using two instruments: a grammar test consisting of 30 items and a narrative writing test assessed through a writing rubric covering content, organization, grammar, vocabulary, and mechanics. The validity test indicated that all instrument items were valid, while the reliability test yielded a Cronbach’s Alpha coefficient of 0.918, indicating very high reliability. The normality test using the Kolmogorov-Smirnov method revealed that the data were not normally distributed; therefore, Spearman’s Rank Correlation was applied to analyze the relationship between the variables. The findings showed a correlation coefficient of 0.663 with a significance value of 0.006 (p < 0.05). These results indicate a strong positive and statistically significant correlation between students’ grammar mastery and their narrative writing skill. Consequently, the null hypothesis was rejected, and the alternative hypothesis was accepted. The study concludes that students with higher levels of grammar mastery tend to demonstrate better performance in writing narrative texts. The findings suggest that integrating grammar instruction with narrative writing practice can contribute to improving students’ writing proficiency in vocational high school contexts.